Assessment of women's knowledge about breast cancer prevention. - Paweł Węgorowski; Joanna Michalik; Ewa Gogułka; Marcin Rząca; Agata Pietrasek (Kazimierz Wielki University, 2017)
Admission Breast cancer is a very insidious disease. For a long time it may not give any symptoms. That's why it is so important to be prophylactic, to have regular breast exams. Among breast cancer women is one of the most common oncological diseases in Poland and is a serious health, social and economic problem. Purpose of research The aim of the work is to assess the level of women on the prevention of breast cancer. It also defines what prevention is and how important it is. Materials and methods 50 women between 20 and 50 years of age were included in the study. The research was conducted in October 2016. Respondents were randomly selected. The method used in the study is a diagnostic survey. A research questionnaire was used as a research tool and a research tool to assist in obtaining research information. Conclusions Women know the main factors that increase the risk of breast cancer: age, genetic factors, contraception, physical inactivity and childlessness. The survey respondents admitted that they use prophylactic tests because they believe they can prevent the disease by 48%, the person is close or has had breast cancer 26%. Almost half of the respondents said that 48% of the respondents declared that the prevention of breast cancer was a lack of knowledge, because 26% of them lacked the knowledge, 26% had good health and 18 lacked the knowledge. %. Discussion Diagnosing the disease will reduce the mortality, so prevention activities that play a vital role in breast cancer prevention play a very important role. Dziukowa and Wesołkowska emphasize that early cancer (less than 10 mm) of the tumors detected does not cause metastasis to the lymph nodes, providing many years of survival and even cure in about 90%.